Consumer markets as a way to maintain the competitiveness of enterprises - Bogdanovich, Ludmila; Kovalchuk, Olga (My University, 2014)
The transformation of the national economic system determines the need for the qualitative changes in the field of agriculture, in particular, in the management of the food market. Crisis situations that occasionally arise in certain markets of food cause the need for a comprehensive approach to this problem.
Keywords: competitiveness; economic system; consumer markets; конкурентоспроможність; економічна система; споживчі ринки; конкурентоспособность; экономическая система; потребительские рынки; кафедра ділової іноземної мови та міжнародної комунікації